The Effect of Drama Technique in Teaching Speaking at Senior High School Students - Armia Armia; Asnawi Asnawi; Chairina Chairina (Universitas Syiah Kuala, 2020)
This expermental study was aimed to find out whether the implementation of drama technique could enhance the students’ speaking skill at SMAN 1 Seulimum. The population of this study was the tenth grade students and the X-IPA 1 class was taken for the research sample. The design of this study was a pre-experimental study which consists of sixt meetings; first meeting was for pre-test, second, third, fourth, and fifth meeting were for treatments, and last meeting was for post-test. As the quantitative method, the researcher analysed the data by means of t-test. The result showed that there was significant difference on the students’ speaking skill taught by using drama technique. The students’ mean of pre-test’s score was 51.64. Then in post-test, the mean score of the students was 63.64. In other words, drama technique was successfully enhancing speaking skill for the tenth grade of senior high school students. Therefore, the drama technique may be one of the appropriate teaching tehniques for improving students’ English speaking ability.